(untitled) (KYAMC Journal, 2017)
CT-guided FNAC is an important method in which aspiration of materials done from deep structure of the body. Now a day, it is a useful tool for diagnosis of lung lesion. This study was done in the department of Pathology, Khwaja Yunus Ali Medical College & Hospital (KYAMCH), a rural tertiary hospital in Bangladesh. A total of 330 cases from January 2008 to December 2013 were evaluated in this study. Of these, 93 (28.20%) were adenocarcinoma, 66 (20%) were squamous cell carcinoma, 35(10.6%) were small cell carcinoma, 31 (9.4%) were non-small cell carcinoma, 03 (0.9%) were non-hodgkin lymphoma, 57 (17.3%) were inflammatory, 24 (7.3%) were tuberculosis and others were 21 (6.4%). The mean age±SD of patients was 58.92±12.92 years. Incidence of malignancy was quite similar in compare to previous study. So in case of any suspicious lesion or growth of lung, CT- guided FNAC should be done for diagnosis and also to exclude malignancy that will help to reduce patients’ morbidity and mortality. KYAMC Journal Vol. 6, No.-1, Jul 2015, Page 562-564